The Influence of Customer Experience and Emotional Attachment on Customer Loyalty at Kopi Kenangan Banjarmasin - Mariyani, Kristin; Diany, Adista Anjar (Transpublika Publisher, 2025)
The rapid growth of coffee shops in Banjarmasin has intensified market competition, requiring brands to deliver superior customer experiences and develop emotional connections to sustain customer loyalty. This research assesses the effects of Customer Experience and Emotional Attachment on Customer Loyalty within the context of Kopi Kenangan in Banjarmasin. A quantitative approach was adopted, employing structured questionnaires distributed to 100 respondents. The analysis of data utilizing multiple linear regression with SPSS version 25 confirms that both independent variables demonstrate a noteworthy and favorable impact on loyalty. The findings suggest that superior customer experiences and profound emotional connections to the brand are key determinants of heightened customer loyalty. Further, Customer Experience emerged as the more predominant determinant of Customer Loyalty in comparison to Emotional Attachment. These outcomes underscore the critical necessity of strategically managing both experiential quality and emotional engagement within customer-brand interactions. The study shed light that continuous improvement in service quality and customer engagement is essential for strengthening emotional connections and maintaining long-term customer loyalty at Kopi Kenangan in Banjarmasin.